PENGARUH MOTIVASI BELAJAR DAN KEDISIPLINAN SISWA TERHADAP PRESTASI BELAJAR SISWA - Endang Kristiani; Triesninda Pahlevi (Prima Magistra: Jurnal Ilmiah Kependidikan, 2021)
The results of preliminary observations at SMK Negeri 10 Surabaya show that the students in class XI OTKP 3 and 4 are still low. The purpose of this study was to determine the effect of learning motivation and student discipline on learning achievement simultaneously. The population for this study were all students of class XI OTKP 3 and 4 at SMK Negeri 10 Surabaya, totaling 72 students. The variables studied were learning motivation (X1) and student discipline (X2) as the independent variable and learning achievement (Y) as the dependent variable. The method used in this research is quantitative research methods, for data collection using a Likert scale questionnaire. Meanwhile, the data analysis method used is the classical assumption test and multiple regression analysis with the help of SPSS 25 for windows. The results of this study are: (1) Learning motivation has a significant positive effect on student achievement in class XI OTKP 3 and 4 at SMK Negeri 10 Surabaya2. (2) Student discipline has a significant positive effect on student achievement in class XI OTKP 3 and 4 at SMK Negeri 10 Surabaya. (3) Student motivation and discipline have a significant positive effect on student achievement in class XI OTKP 3 and 4 at SMK Negeri 10 Surabaya.